2007
DOI: 10.1179/174328407x166687
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion strengthening in vanadium microalloyed steels processed by simulated thin slab casting and direct charging Part 1 – Processing parameters, mechanical properties and microstructure

Abstract: This version is available at https://strathprints.strath.ac.uk/5778/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 28 publications
3
28
0
Order By: Relevance
“…In fact, the work showed that sub-15 nm particles were nitrogen rich carbonitrides which do not appear to coarsen during the final stages of processing. 154,[175][176][177][178] The carbon extraction replica technique has the advantage of giving good contrast for extracted particles, low background for analysis using PEELS and EDX spectroscopy, and no perturbation of the optical properties of the objective lens from the ferromagnetic material in a typical foil specimen. However, there is some uncertainty about the extraction efficiency for the smallest particles, as very few were found with sizes ,4 nm.…”
Section: Methods For Analysis Chemical Composition Of Vanadium Precipmentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, the work showed that sub-15 nm particles were nitrogen rich carbonitrides which do not appear to coarsen during the final stages of processing. 154,[175][176][177][178] The carbon extraction replica technique has the advantage of giving good contrast for extracted particles, low background for analysis using PEELS and EDX spectroscopy, and no perturbation of the optical properties of the objective lens from the ferromagnetic material in a typical foil specimen. However, there is some uncertainty about the extraction efficiency for the smallest particles, as very few were found with sizes ,4 nm.…”
Section: Methods For Analysis Chemical Composition Of Vanadium Precipmentioning
confidence: 99%
“…A similar effect was found in a study of TSDC 0?06 wt-%C steels where, following reheating at 1050uC, despite the smaller ferrite grain size of an 0?1V-0?010Ti-0?017N (wt-%) steel, a reduction in yield strength of 84 MPa was recorded compared with an 0?1V-0?02N (wt-%) steel. 154 With a 0?1V-0?03Nb-0?007Ti (wt-%) steel, the reduction in yield strength was 70 MPa. 154 The comparison of V and V-Nb steels usually shows that an addition of about 0?03-0?04 wt-%Nb results in a gain in yield strength but a loss in toughness.…”
Section: Multimicroalloyed Steelsmentioning
confidence: 99%
See 3 more Smart Citations